Unified view on linear response of interacting identical and distinguishable particles from multiconfigurational time-dependent Hartree methods - Alon, Ofir E.; Streltsov, Alexej Iwanowitsch; Cederbaum, Lorenz S. (The journal of chemical physics, 2014)
A unified view on linear response of interacting systems utilizing multiconfigurational time-dependent Hartree methods is presented. The cases of one-particle and two-particle response operators for identical particles and up to all-system response operators for distinguishable degrees-of-freedom are considered. The working equations for systems of identical bosons and identical fermions, as well for systems of distinguishable particles are explicitly derived. These linear-response theories - applicable for discrete excitation spectra - provide numerically exact excitation energies and system's properties, when numerical convergence is achieved in the calculations.